2021
DOI: 10.1021/acsomega.0c05136
|View full text |Cite
|
Sign up to set email alerts
|

Evolution Characteristics of Mechanical Properties under Supercritical Carbon Dioxide Treatment in Shale Reservoirs

Abstract: Supercritical carbon dioxide (SC-CO2) has been progressively used in the development of shale oil and gas. However, the interaction between CO2 and shale can change the mineral composition and the pore structure, thus affecting the mechanical properties of shale. To study the influence of SC-CO2 on shale, shale samples collected from the Songliao Basin in China are treated with SC-CO2 at various time intervals. Then, a series of tests are performed, such as the mineral composition analysis test, the pore struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Contrary to previous studies, they reported a minor change in pore morphology, inferred through the change in hysteresis behavior of N 2 LPGA isotherms. Meng et al, 187 although focused on SC-CO 2 -induced geomechanical changes in shales from Songliao Basin, China, noted that the mineral matter content, especially calcite, strongly decreased, because of dissolution, with increasing exposure to SC-CO 2 . Similar to other researches, they observed the primary porous structures and fractures to be dissolved and replaced by newer structures formed because of exposure.…”
Section: Influence Of Sc-co 2 On Shale Petrophysics Geomechanics and ...mentioning
confidence: 99%
“…Contrary to previous studies, they reported a minor change in pore morphology, inferred through the change in hysteresis behavior of N 2 LPGA isotherms. Meng et al, 187 although focused on SC-CO 2 -induced geomechanical changes in shales from Songliao Basin, China, noted that the mineral matter content, especially calcite, strongly decreased, because of dissolution, with increasing exposure to SC-CO 2 . Similar to other researches, they observed the primary porous structures and fractures to be dissolved and replaced by newer structures formed because of exposure.…”
Section: Influence Of Sc-co 2 On Shale Petrophysics Geomechanics and ...mentioning
confidence: 99%
“…Furthermore, these changes in the rock structure may lead to a dramatic decrease in the rock material strength. 27 3.2. Study on the Interaction between Supercritical CO 2 and Formation Fluid.…”
Section: Resultsmentioning
confidence: 99%
“…This resulted in a significant increase in the complexity of the fracture network. Furthermore, these changes in the rock structure may lead to a dramatic decrease in the rock material strength …”
Section: Resultsmentioning
confidence: 99%
“…The CO 2 −shale interaction induced mechanical weakening in shale will increase the stress sensitivity of shale; with the injection of CO 2 , the variation of gas pressure will induce the perturbation in geostresses, which will significantly impact on the permeability of shale. 154 In the unstressed state, the chemical reaction enlarges the pores in the shale, leading to the increase in porosity and the initial permeability of the shale. 163 In the stressed state, the permeability of shale is controlled by the chemical−mechanical coupling effects, and the permeability enhancement of shale by ScCO 2 dissolution effects may not be guaranteed.…”
Section: Adsorption Behaviormentioning
confidence: 99%
“…Additionally, it should be noted that the CO 2 –shale interaction induced mechanical weakening of shale also significantly affects the permeability of shale, which has been not of concern at present. The CO 2 –shale interaction induced mechanical weakening in shale will increase the stress sensitivity of shale; with the injection of CO 2 , the variation of gas pressure will induce the perturbation in geostresses, which will significantly impact on the permeability of shale . In the unstressed state, the chemical reaction enlarges the pores in the shale, leading to the increase in porosity and the initial permeability of the shale .…”
Section: Alterations In Physical and Chemical Properties Of Shalementioning
confidence: 99%